Manajemen Kurikulum Pendidikan Islam Pada Masa Covid-19 di Masjid Hayatul Hasanah dan Baitut Tarbiyah Dinas Pendidikan Kabupaten Purwakarta - Imam Tabroni; Erfian Syah; Siswanto Siswanto (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2022)
The Islamic education curriculum is managed by the Mosque Prosperity Council (DKM) to plan, schedule, determine, and evaluate the materials and methods delivered by the preacher for one year. This study aims to analyze the problem and find solutions for the management of the Friday sermon curriculum at the Hayatul Hasanah Mosque and Baitut Tarbiyah Education Office of Purwakarta Regency. The approach used in this study is qualitative with a grounded theory design. Data collection techniques using observation, interviews, and documentation. Data analysis by triangulation. The findings of the research are that the planning already looks good, namely by setting the schedule for the khatib and imam for the Friday prayers of the two mosques for one year, but there are no clear policies, plans, work techniques, costs. It was found that the DKM organization already had a clear organizational structure, although it still did not explain in detail the relationship between one structure and another with regard to work relations and coordination of the achievement of certain standards in the Friday sermon curriculum. Coordination between members of the DKM structure in providing motivation and coordination has not been optimal even though it has been carried out before the Friday sermon is held. Control is carried out by setting standards, measuring, reviewing results with standards, and improving standards and evidence of activities if there are problems related to the Friday sermon curriculum. This process apparently has not been specifically found